Theoretical Principles of Sociology, Volume 1 Macrodynamics - Turner, Jonathan H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
In a general study of Sociological Theory, social processes are usually broken down into three tiers: macrodynamics (societies and large-scale institutions), microdynamics (interpersonal encounters), and mesodynamics (corporations, communities, smaller organizations). In this seminal work, the author pulls these separate areas of research into one comprehensive general theory of social reality. More than analytical distinctions or research terminology, the author demonstrates that the social world actually unfolds along these three (macro, micro, and meso) levels of interaction. By developing a set of explanatory, testable, repeatable principles, the author creates a general empirical framework for sociological research. The three volumes of Principles of Sociology explore each level of social dynamics individually, with cross-references to bring the three together. This work will be essential for researchers in Sociological Theory and Social Psychology. Individual volumes will present new research of interest for researchers in Race and Ethnicity, Stratification, Demography, Political Sociology, Organizations and Community Movements, Motivation and Emotions. In this volume, the editor specifically focusses on macro-level dynamics and their impact on social interaction. Macro-level dynamics drive the formation of large-scale structures and their cultures.
Macrodynamics: First Steps in Developing a General Sociological Theory -- Selection Pressures and the Evolution of the Macrodynamic Realm -- Elemenary Principles on Macrodynamic Forces -- The Dynamics of Institutional Domains -- The Dynamics of Stratification Domains -- The Dynamics of Stratification Systems -- The Dynamics of Societal Systems -- The Dynamics of Inter-Societal Systems -- Principles of Macrodynamics -- Microdynamics: Encounters at the Micro-level Realm of Reality -- The Embedding of Encounters -- Demographic and Ecological Dynamics of Encounters -- Status Dynamics in Encounters -- Role Dynamics in Encounters -- Cultural Dynamics in Encounters -- Motivational Dynamics in Encounters -- Emotional Dynamics in Encounters -- Principles of Microdynamics -- Mesodynamics: The Meso-Level Realm of Reality -- Micro-and Macro-Level Constrains under Mesodynamics -- Corporate Unit Dynamics: Groups, Organizations, Communities -- Corporate Unit Dynamics in Categoric-Unit Dynamics -- Principles of Mesodynamics.
Keywords: Social sciences; Consciousness; Social Sciences; Sociology, general; Personality and Social Psychology